The Ethical Responsibilities and the Liability of Insurance Intermediaries in Cameroon (African Journal of Law and Politics, 2025)
The importance of insurance in modern economies is unquestioned and has been recognised forcenturies. Insurance “is practically a necessity to business activity and enterprise.”As players with bothbroad knowledge of the insurance marketplace, including products, prices and providers, and an acutesense of the needs of insurance purchasers, intermediaries have a unique role – indeed many roles – toplay in the insurance markets in particular and, more generally, in the functioning of national andinternational economies. In today’s complex insurance marketplace, however, intermediaries havebecome more than middlemen between insurance companies and insurance buyers. Despite a strictlegislative regime and pro-consumer developments, insurance intermediaries still fail to disclosematerial and onerous terms in their dealings with prospective policyholders. This paper seeks toinvestigate the rules that aim to regulate the up-front, honest disclosure of onerous terms to theprospective policyholder, and tries to answer the question of whether the intermediaries and advisorscomply with their duties to disclose onerous terms to prospective policyholders. Adopting a doctrinalresearch method, it is observed that intermediaries in Cameroon are involved in misappropriation of theinsured premium, rate cutting among others. The establishment of an effective, monitoring andenforcement mechanism is vital to ensure compliance with the regulations in enforce.